PEMANFAATAN APLIKASI RUANG GURU DAN TENAGA KEPENDIDIKAN DALAM PERENCANAAN KURIKULUM (STUDI KASUS KUALITATIF DI SDN 01 BAMBU APUS JAKARTA TIMUR) - Naya Aulia Kamil; Syarif Sumantri; Engga Dallion (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the utilization of the Teacher and Education Personnel Platform (Ruang GTK) in curriculum planning at SD Negeri Bambu Apus 01. The research employed a qualitative approach using a case study method. Data were collected through interviews, observations, and documentation involving the vice principal for curriculum affairs and four teachers. Data analysis was conducted using Kristi Poerwandari’s qualitative analysis model, which includes data organization, coding, interpretation, and conclusion drawing. The findings revealed that teachers utilized various features of Ruang GTK, including teaching resources, independent training, best practices, and performance management, to support curriculum planning. The use of Ruang GTK helped teachers access more diverse learning references, improve the quality of instructional planning, and support the implementation of the Merdeka Curriculum. The challenges encountered included teachers’ self-motivation, adaptation to the application, digital literacy, internet connectivity, and time management. To address these challenges, the school provided training programs, socialization activities, peer assistance, internet facilities, and structured scheduling for the use of Ruang GTK. Therefore, Ruang GTK serves as a supporting platform that contributes to improving the quality of curriculum planning in elementary schools.